2021
DOI: 10.1128/jcm.00416-21
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an In-House Enzyme-Linked Immunosorbent Assay and IgG Avidity Test Based on SAG1 and GRA7 Proteins for Discriminating between Acute and Chronic Toxoplasmosis in Humans

Abstract: To improve serodiagnostic methods for diagnosis of acute from chronic toxoplasmosis, an economical in-house ELISA for measuring Toxoplasma -specific IgG, IgM and IgG avidity has been developed and assessed based on use of various T. gondii antigens, including SAG1, GRA7 and a combination of SAG1 and GRA7 (SAG1+GRA7) as well as Toxoplasma lysate antigens (TLAs). Performances of in-house IgM, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…A similar study by Zhang et al revealed that the detection limits of LAMP and conventional PCR assays using REP-529 target were 1 and 10 pg, respectively [ 43 ]. Various target genes such as SAG1, SAG2, SAG3, SAG4, ITS, B1, REP-529, P30, GRA4, GRA6 and GRA7 have been used to detect toxoplasmosis [ 44 – 48 ]. The results have shown that both REP-529 and B1 are highly sensitive; REP-529 is more sensitive than B1 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study by Zhang et al revealed that the detection limits of LAMP and conventional PCR assays using REP-529 target were 1 and 10 pg, respectively [ 43 ]. Various target genes such as SAG1, SAG2, SAG3, SAG4, ITS, B1, REP-529, P30, GRA4, GRA6 and GRA7 have been used to detect toxoplasmosis [ 44 – 48 ]. The results have shown that both REP-529 and B1 are highly sensitive; REP-529 is more sensitive than B1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The SAG1, SAG2, SAG3, SAG4, GRA4, GRA6 and GRA7 genes include only one copy in genome of T. gondii , which are specific as well [ 46 ]. Studies have shown that the number of copies of each gene fragment includes direct relationships with the diagnosis sensitivity [ 48 , 52 ]. Another factor that is important in selecting appropriate gene fragments is specificity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the various limitations of avidity tests based on these antigenic preparation, new diagnostic tools that might improve the performance of avidity tests to distinguish between recent and past phases of toxoplasmosis are tested. In the past 20 years, several studies have reported the use of single recombinant antigens [ 44 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], mixture of proteins [ 44 , 67 , 68 ] or chimeric proteins [ 69 ] in the determination of IgG avidity ( Table 1 ). All these antigens have been obtained in Escherichia coli expression systems and purified by affinity chromatography.…”
Section: Recombinant Antigens In Igg Avidity Testsmentioning
confidence: 99%
“…These results indicate that the ARCHITECT Toxo IgG Avidity assay can not only reliably detect acute phase samples much earlier than the Vidas system, but can also be performed longer for past infection samples with low-level IgG antibodies. Another study reported that the SAG1 recombinant protein mixed with the recombinant GRA7 showed potential for assessing avidity of IgG antibodies [ 68 ]. These preliminary results showed better discrimination between acute and chronic infection using the SAG1 + GRA7 combination than those using whole-cell antigens.…”
Section: Recombinant Antigens In Igg Avidity Testsmentioning
confidence: 99%
“…Moreover, during T. gondii infections, the positivity for IgM antibody is proposed to be a marker of acute infection due to the occurrence of IgM antibody within days to a couple of weeks, and IgG antibodies are often interpreted as rising to protective levels after infection and remaining detectable for years, while the positivity for both IgG and IgM antibodies resulted is generally considered to indicate chronic reactivated cases (Kimbita et al, 2001;Dösķaya et al, 2014;Dhakal et al, 2015). IgM antibodies may be detected in humans or animals for a long time following primary T. gondii infections (Del Bono et al, 1989;Fricker-Hidalgo et al, 2013;Dhakal et al, 2015;Ybanez et al, 2020;Teimouri et al, 2021), and the natural IgM antibody may interact with parasite antigens in the absence of the Toxoplasma infection (Potasman et al, 1986;Sensini et al, 1996.;Liesenfeld et al, 1997;Dhakal et al, 2015;Teimouri In this work, although it is shown that Tibetan sheep, yaks, cows, and cattle were overall low both for T. gondii IgG and IgM positivity, there was no significant difference among rSAG1-, rGRA7-, and rBAG1-ELISAs. These results indicate that T. gondii may be infected at low titers in the animals collected in this study.…”
Section: Animalmentioning
confidence: 99%